Therapeutic Modulation of Haematological Parameters and Fertility Outcomes in Postpartum Subclinical Endometritis in Jaffarabadi Buffaloes - Kapadiya, Pratik S; Vala, Karsan B; Parikh, Suryakant S; Vijyeta, Hardipsinh P; Sharma, Arun K; Savsani, Harish H (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study investigated the effects of intrauterine lysozyme, povidone iodine, and antibiotic therapy on haematological parameters and conception rates in postpartum subclinical endometritic (SCE) Jaffarabadi buffaloes. Thirty animals (24 SCE-affected and 6 healthy controls) were randomly allocated into five groups: Group I (lysozyme 2 mg in 20 mL PBS once), Group II (2% povidone iodine, 50 mL once), Group III (sensitive antibiotic, levofloxacin, 20 mL for 3 days), Group IV (untreated positive control), and Group V (healthy negative control). Haemoglobin, packed cell volume, total leukocyte count, and differential leukocyte counts (neutrophils, lymphocytes, monocytes, eosinophils, basophils) were assessed at 0 h, 72 h, and at subsequent estrus. Conception rate was evaluated on the basis of first service conception (FSCR) at subsequent estrus. Groups I and II buffaloes exhibited significant (p<0.05) post-treatment increase in haemoglobin and packed cell volume, whereas other haematological parameters remained unaffected. First service conception rate was recorded as 33.33% in Groups I, II, and V, 16.67% in Group III, and 0.00% in Group IV. These findings indicate that intrauterine administration of lysozyme and povidone iodine improves haematological status and reproductive performance in SCE-affected Jaffarabadi buffaloes